2015
DOI: 10.1097/aln.0000000000000448
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Attenuated Acute Kidney Injury after Orthotopic Liver Transplantation via Inhibiting Gap Junction Composed of Connexin 32

Abstract: Cx32 plays a critical role in AOLT-induced AKI and that inhibition of Cx32 function may represent a new and major mechanism whereby propofol reduces oxidative stress and subsequently attenuates post-AOLT AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
87
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 49 publications
5
87
0
1
Order By: Relevance
“…Oxidative stress and the inflammatory reaction interact in a complex way to act in the pathogenesis of lung damage. Studies have demonstrated that ROS are fundamental to oxidative stress and the inflammatory reaction (38,39). The current study demonstrated that NAC and AP application inhibited NAPDH oxidase in the earlier phase and reduced or eliminated ROS production.…”
Section: Discussionmentioning
confidence: 58%
“…Oxidative stress and the inflammatory reaction interact in a complex way to act in the pathogenesis of lung damage. Studies have demonstrated that ROS are fundamental to oxidative stress and the inflammatory reaction (38,39). The current study demonstrated that NAC and AP application inhibited NAPDH oxidase in the earlier phase and reduced or eliminated ROS production.…”
Section: Discussionmentioning
confidence: 58%
“…Several animal studies suggested that propofol is effective in attenuating AKI in different models (8)(9)(10). Although it is commonly observed that therapeutic and preventive strategies related to AKI are successful in animal models and fail in human trials, a recent randomized controlled study showed that propofol anesthesia was associated with a reduction in AKI incidence in patients undergoing valvular heart surgery compared with sevoflurane anesthesia (11).…”
Section: Introductionmentioning
confidence: 99%
“…We observed that ROS not only enhanced oxaliplatin sensitivity to CRC, but also contributed to epithelial-mesenchymal transition and cancer metastasis, which indicated that ROS may play an essential role in the development of cancers (10). Luo et al reported that GJs composed of Cx32 regulated the distribution of ROS (5). Therefore, we considered that ROS distribution modulated by GJs might contribute to the cytotoxicity of oxaliplatin.…”
Section: Discussionmentioning
confidence: 99%
“…The GJ enables cells to exchange ions and small molecules (with a molecule weight less than 1 kDa) directly, including calcium, glutathione, cyclic adenosine monophosphate and cyclic guanosine monophosphate. Molecules transferred through the GJ are essential for numerous physiological and pathological events (5,6). The connexin gene family constitutes 21 isoforms, the most significant of which is Cx43 (6).…”
Section: Introductionmentioning
confidence: 99%